Does Delayed-Time-Point Imaging Improve 18F-FDG-PET in Patients With MALT Lymphoma?: Observations in a Series of 13 Patients. (February 2016) - Mayerhoefer, Marius E.; Giraudo, Chiara; Senn, Daniela; Hartenbach, Markus; Weber, Michael; Rausch, Ivo; Kiesewetter, Barbara; Herold, Christian J.; Hacker, Marcus; Pones, Matthias; Simonitsch-Klupp, Ingrid; Müllauer, Leonhard; et al.
Abstract : Purpose: To determine whether in patients with extranodal marginal zone B-cell lymphoma of the mucosa-associated lymphoid tissue lymphoma (MALT), delayed–time-point 2- 18 F-fluoro-2-deoxy-d-glucose-positron emission tomography ( 18 F-FDG-PET) performs better than standard–time-point 18 F-FDG-PET. Materials and Methods: Patients with untreated histologically verified MALT lymphoma, who were undergoing pretherapeutic 18 F-FDG-PET/computed tomography (CT) and consecutive 18 F-FDG-PET/magnetic resonance imaging (MRI), using a single 18 F-FDG injection, in the course of a larger-scale prospective trial, were included. Region-based sensitivity and specificity, and patient-based sensitivity of the respective 18 F-FDG-PET scans at time points 1 (45–60 minutes after tracer injection, TP1) and 2 (100–150 minutes after tracer injection, TP2), relative to the reference standard, were calculated. Lesion-to-liver and lesion-to-blood SUVmax (maximum standardized uptake values) ratios were also assessed. Results: 18 F-FDG-PET at TP1 was true positive in 15 o f 23 involved regions, and 18 F-FDG-PET at TP2 was true-positive in 20 of 23 involved regions; no false-positive regions were noted. Accordingly, region-based sensitivities and specificities were 65.2% (confidence interval [CI], 45.73%–84.67%) and 100% (CI, 100%-100%) for 18 F-FDG-PET at TP1; and 87.0% (CI, 73.26%–100%) and 100% (CI, 100%-100%) for 18 F-FDG-PET at TP2, respectively. FDG-PET at TP1 detected lymphoma in at least one nodal or extranodal region in 7 of 13 patients, and 18 F-FDG-PET at TP2 in 10 of 13 patients; accordingly, patient-based sensitivity was 53.8% (CI, 26.7%–80.9%) for 18 F-FDG-PET at TP1, and 76.9% (CI, 54.0%–99.8%) for 18 F-FDG-PET at TP2. Lesion-to-liver and lesion-to-blood maximum standardized uptake value ratios were significantly lower at TP1 (ratios, 1.05 ± 0.40 and 1.52 ± 0.62) than at TP2 (ratios, 1.67 ± 0.74 and 2.56 ± 1.10; P = 0.003 and P = 0.001). Conclusions: Delayed–time-point imaging may improve 18 F-FDG-PET in MALT lymphoma.